The Effects of Digital Information Technology, Digital Marketing and Human Resource Capacity on Smes Performance in North Sumatera - Noviani; Erlina; Iskandar Muda; Keulana Erwin; Agung Wahyudhi Atmanegara (Yayasan Ilomata, 2026)
This study investigates the effects of digital information technology, digital marketing, and human resource capacity on SME performance in North Sumatera. Although numerous prior studies have examined these variables separately, a significant gap persists regarding their synergistic effects, especially among SMEs in developing regions. To address this gap, the present study developed an integrated model using an explanatory research design. Data were collected through a survey of 232 SMEs that actively adopt digital technology in North Sumatra Province, representing a targeted sample of digitally active small and medium enterprises in a developing region. The data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) due to its suitability for examining complex relationships in a predictive, non parametric manner with relatively small sample sizes. The results indicate that all three variables exert positive and significant effects on SME performance, with digital marketing emerging as the strongest predictor. These findings underscore the importance of resource integration in enhancing SME competitiveness in emerging economies.